Pt-modified thermal-corrosion-resistant nitrogen-containing nickel-based cladding layer and preparation method thereof
Through the preparation of Pt-modified thermal corrosion-resistant nickel-based cladding, the thermal corrosion problem in ultra-supercritical coal-fired power generation environment is solved, and the good combination of the cladding layer and the substrate is achieved and the efficient thermal corrosion resistance is extended, and the service life of the equipment is extended.
Patent Information
- Application Number
- CN202411850406.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
In the ultra-supercritical coal-fired power generation environment, thermal corrosion seriously erodes the core components of the equipment, resulting in a shortened service life of the equipment and high operation and maintenance costs.
The Pt-modified thermal corrosion-resistant nitrogen-containing nickel-based cladding layer was prepared by vacuum smelting and plasma cladding technology, and composed of a nickel-based cladding layer including 24-26% chromium, 4-4.5% molybdenum, 4-6.5% niobium, 13-14% iron, 0.5%-0.6% nitrogen, 0.15-0.3% platinum, and nitrogen was added in the form of chromium nitride.
The prepared cladding layer has a dense and uniform structure, no defects, and is well combined with the matrix, which significantly improves the heat corrosion resistance and extends the service life of ultra-supercritical boiler components.
Smart Images

Figure HDA0005190423840000011 
Figure HDA0005190423840000012 
Figure HDA0005190423840000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a Pt-modified heat-corrosion-resistant nitrogen-containing nickel-based cladding layer and a preparation method thereof. Background Art
[0002] Under the background of continuous changes in the global energy landscape and the strong drive of the "dual carbon" goal, ultra-supercritical coal-fired power generation technology has become a key force in the clean and efficient use of coal and in helping the power industry to save energy and reduce emissions with its excellent ability to improve thermal efficiency. This technology operates under ultra-high pressure (greater than 22.1MPa) and ultra-high temperature (up to 650℃ and above) conditions, greatly optimizing the coal combustion and energy conversion process, and effectively reducing coal consumption and pollutant emissions.
[0003] However, the ultra-supercritical environment has also given rise to thorny problems. Thermal corrosion is like a "chronic disease" that seriously corrodes the core components of the equipment. Sulfur oxides, chloride salts and other impurities derived from coal combustion interact with high-temperature water vapor to form highly corrosive media, condense and react on the boiler heating surface, and corrode the metal pipe wall; at the same time, fly ash carries a large amount of minerals, which impact and scrape at high speed, synergistically corrode, causing the pipe wall to thin rapidly and reduce strength, greatly shortening the service life of the equipment, and frequently shutting down for maintenance and replacement, resulting in high operation and maintenance costs and power generation losses, which restricts the promotion of technology.
[0004] The Chinese invention patent with application number 202110914620.6 discloses a method for manufacturing an iron-nickel-based alloy seamless pipe that can be used in advanced ultra-supercritical units. The chemical composition of the high-temperature section is calculated by mass percentage: C 0.03-0.08%, Si≤0.3%, Mn≤0.3%, Cr 15-20%, Mo≤0.9%, W≤0.5%, Fe 36-45%, B≤0.005%, Al1.2-2.0%, Ti 1.8-3.0%, and the balance is Ni; wherein Ti / Al=3 / 2, Fe / Ni>1.
[0005] The Chinese invention patent with application number 202110914620.6 discloses a method for manufacturing an iron-nickel-based alloy seamless pipe that can be used for advanced ultra-supercritical units. The chemical composition includes: C 0.02%~0.10%, Si≤0.10%, Cr12.00%~18.00%, Mo 0.50%~1.00%, Co 1.00%~2.00%, Ti 2.00%~2.50%, Al1.00%~1.60%, W 0.10%~0.80%, B 0.002%~0.008%, Fe 40.00%~45.00%, and the balance is Ni.
[0006] Nickel-based alloys have excellent high-temperature corrosion resistance. They rely on nickel to build a stable crystal structure and work with chromium, molybdenum and other elements to form a dense protective film to resist corrosion. However, nickel resources are scarce, mining and refining are complex, and costs are high. Therefore, the development of low-cost nickel-based alloys has become a core breakthrough point. The remanufacturing and repair links are used with the help of plasma cladding technology to highlight its value and enhance corrosion resistance, which not only extends the service life of equipment, but also conforms to the concept of circular economy. Summary of the invention
[0007] The purpose of the present invention is to provide a Pt-modified, heat-resistant, nitrogen-containing nickel-based cladding layer and a preparation method thereof, so as to overcome the shortcomings of the prior art and solve the problem of thermal corrosion in an ultra-supercritical environment. The prepared cladding layer is defect-free, the cladding layer has a good metallurgical bond with the substrate, and the cladding layer has a dense and uniform structure, which meets the requirements for repair and remanufacturing of ultra-supercritical boiler components and prolongs the service life of ultra-supercritical coal-fired power generation units.
[0008] To achieve the above object, the present invention is implemented through the following technical solutions:
[0009] Technical solution 1: A Pt-modified, heat-resistant, nitrogen-containing nickel-based cladding layer, whose components are as follows by weight percentage: 24-26% chromium, 4-4.5% molybdenum, 4-6.5% niobium, 13-14% iron, 0.5%-0.6% nitrogen, 0.15-0.3% platinum, and the rest is nickel, wherein nitrogen is added in the form of chromium nitride.
[0010] Technical solution 2: A method for preparing a Pt-modified, heat-resistant, nitrogen-containing nickel-based cladding layer, the specific operation steps of which are as follows:
[0011] 1) Vacuum smelting: various components are smelted into alloy blocks in proportion, and the purity of the alloy blocks is ≥99.5%;
[0012] 2) Atomization powder making, obtaining alloy powder by vacuum atomization method, the particle size of the alloy powder is 30μm to 100μm, and drying for standby use;
[0013] 3) Matrix treatment: polish the nickel-based alloy matrix to a bright finish, then rinse with alcohol and dry for later use;
[0014] 4) Preparation of cladding layer: forming a cladding layer by plasma cladding the alloy powder.
[0015] Furthermore, the vacuum atomization equipment in step 2) is a ZGW-25 vacuum air atomization powder making equipment.
[0016] Furthermore, in step 2), the drying temperature is 80° C. to 100° C., and the drying time is 6 to 8 hours.
[0017] Furthermore, in the step 3), the composition of the nickel-based alloy matrix is 20.9% chromium, 8.7% molybdenum, 4.8% niobium, 4.3% iron, 0.1% aluminum, 0.4% titanium, and the rest is nickel.
[0018] Furthermore, in step 3), the drying temperature is 60-110° C., and the drying time is 1-3 hours.
[0019] Furthermore, the plasma cladding equipment in step 4) is a DML-V03BD powder cladding machine.
[0020] Furthermore, in the step 4), the current of plasma cladding is 100-120A, the cladding speed is 3-4mm / s, the synchronous powder feeding rate is 9.5-10.5g / min, the plasma gas flow rate is 2-4L / min, and the powder feeding gas flow rate is 2-8L / min.
[0021] Furthermore, in the step 4), the overlap ratio of multiple passes of the cladding layer is 30-45%.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1) The cladding layer obtained by plasma cladding has a dense, uniform and defect-free structure and is well bonded to the substrate.
[0024] 2) The nitrogen-containing nickel-based cladding layer obtained by the present invention has excellent heat corrosion resistance.
[0025] 3) The present invention obtains a nitrogen-containing nickel-based cladding layer with better performance, which can meet the requirements of repair and remanufacturing of ultra-supercritical boiler components and extend the service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a macroscopic image of the cladding layer of an embodiment of the present invention;
[0027] Figure 2 It is a comparison chart of the bonding strength of the cladding layers of Examples 1-3 of the present invention and the comparative example;
[0028] Figure 3 It is a comparison chart of the XRD spectra of the corrosion products of the cladding layers of Examples 1-3 of the present invention and the comparative example after being corroded in Na2SO4+NaCl molten salt at 700°C for 50 hours;
[0029] Figure 4 It is a comparison diagram of the surface morphology of the cladding layers of Examples 1-3 of the present invention and the comparative example after being corroded in Na2SO4+NaCl molten salt at 700°C for 50 hours;
[0030] Figure 5It is a comparison diagram of the cross-sectional morphology of the cladding layers of Examples 1-3 of the present invention and the comparative example after being corroded in Na2SO4+NaCl molten salt at 700°C for 50 hours. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the specific embodiments required to be used in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the specific embodiments described below are some implementation methods of the present invention. For ordinary technicians in this field, other specific embodiments can be obtained based on these specific embodiments without paying creative work.
[0033] The components of the embodiments of the present invention generally described and shown in the specific embodiments herein can be arranged and designed in countless different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the specific embodiments is not intended to limit the scope of the invention claimed, but only represents selected embodiments of the present invention.
[0034] In the following examples 1-3 and comparative examples, the plasma cladding equipment produced by Shenyang Duomu Welding Co., Ltd. is a DML-V03BD powder cladding machine to achieve the preparation of the cladding layer. The vacuum atomization equipment is a ZGW-25 vacuum gas atomization powder making equipment. The nickel-based alloy matrix used is Inconel 625, which has a composition of 20.9% chromium, 8.7% molybdenum, 4.8% niobium, 4.3% iron, 0.1% aluminum and 0.4% titanium, and the rest is nickel, with a strength of 950.7Mpa.
[0035] The preparation of the cladding layer samples obtained in Examples 1-3 and Comparative Examples was carried out in accordance with the DB37 / T 3589-2019 Remanufactured Laser Cladding Layer and Substrate Bonding Strength Test Sample Preparation Method Specification. The bonding strength between the cladding layer and the substrate was tested in accordance with the DB37 / T 3590-2019 Remanufactured Laser Cladding Layer and Substrate Bonding Strength Test Method and Evaluation Specification. The hot corrosion performance of the cladding layer was tested in accordance with the GB / T38231-2019 Corrosion of Metals and Alloys Thermal Cyclic Exposure Oxidation Test Method for Metal Materials under High Temperature Corrosion Conditions.
[0036] Example 1
[0037] The present invention provides a nitrogen-containing nickel-based alloy powder, wherein the alloy composition is 21.8% chromium powder, 4.1% molybdenum powder, 6.4% niobium powder, 13.4% iron powder, 1.2% aluminum powder, 0.55% chromium nitride and 0.1% platinum powder, and the rest is nickel powder. The specific preparation steps are as follows:
[0038] 1) Powder preparation: The powder is melted in a vacuum melting furnace according to the above ratio to obtain an alloy, and the purity of the alloy block is 99.8%;
[0039] 2) The alloy obtained by smelting is used as a master alloy to prepare nitrogen-containing nickel-based powder with a particle size of 50 to 80 μm by gas atomization, and then dried at 80° C. for 6 hours for use.
[0040] 3) Matrix treatment: Polish the nickel-based alloy matrix, rinse with alcohol and dry at 100°C for 1 hour.
[0041] 4) Plasma cladding: The process parameters were set as cladding current of 100 A, cladding speed of 3 mm / s, synchronous powder feeding rate of 10 g / min, cladding multi-pass overlap rate of 32%, plasma gas flow rate of 3.6 L / min, and powder feeding gas flow rate of 5.3 L / min to prepare a cladding layer from nitrogen-containing nickel-based powder.
[0042] The nitrogen-containing nickel-based cladding layer obtained in Example 1 is dense, uniform and crack-free. Figure 1 The samples shown were tested for bonding strength and the results are shown in Figure 1 The bonding strength is 927.5Mpa. The cladding layer was subjected to a 50h hot corrosion test in a Na2SO4+NaCl mixed molten salt at 700℃, and the corrosion weight loss was 4.1387mg / cm 2 At the same time, the surface morphology and cross-sectional morphology of the cladding layer after corrosion were characterized. Figure 3-5 .
[0043] Example 2
[0044] The nitrogen-containing nickel-based alloy powder of the present invention, wherein the alloy components are 21.8% chromium powder, 4.1% molybdenum powder, 6.4% niobium powder, 13.4% iron powder, 13.4% iron powder, 1.3% aluminum powder, 0.55% chromium nitride, 0.07% Pt powder, and the rest is nickel powder. The specific preparation steps are as follows:
[0045] 1) Powder preparation: The powder is melted in a vacuum melting furnace according to the above ratio to obtain an alloy, and the purity of the alloy block is 99.78%;
[0046] 2) The alloy obtained by smelting is used as a master alloy to prepare a nitrogen-containing nickel-based powder with a particle size of 30 to 60 μm by gas atomization, and then dried at 90° C. for 8 hours for use;
[0047] 3) Matrix treatment: polish the nickel-based alloy matrix, rinse with alcohol and dry at 60°C for 3 hours;
[0048] 4) Plasma cladding: The process parameters were set as cladding current of 120 A, cladding speed of 4 mm / s, synchronous powder feeding rate of 9.5 g / min, cladding multi-pass overlap rate of 45%, plasma gas flow rate of 4.0 L / min, and powder feeding gas flow rate of 8.0 L / min to prepare the nitrogen-containing nickel-based powder into a cladding layer.
[0049] The nitrogen-containing nickel-based cladding layer obtained in Example 2 is dense, uniform and crack-free. Figure 1 The samples shown were tested for bonding strength and the results are shown in Figure 1 The bonding strength is 884.3Mpa. The cladding layer was subjected to a 50h hot corrosion test in a Na2SO4+NaCl mixed molten salt at 700℃, and the corrosion weight loss was 4.4827mg / cm 2 At the same time, the surface morphology and cross-sectional morphology of the cladding layer after corrosion were characterized. Figure 3-5 .
[0050] Example 3
[0051] The nitrogen-containing nickel-based cladding layer of the present invention has an alloy composition of 21.3% chromium powder, 4.2% molybdenum powder, 6.3% niobium powder, 13.4% iron powder, 1.2% aluminum powder, 0.5% chromium nitride powder, 0.05% platinum powder, and the rest is nickel powder. The specific preparation steps are as follows:
[0052] 1) Powder preparation: various alloy powders are taken in proportion to prepare alloy ingots, and the purity of the alloy ingots is 99.89%;
[0053] 2) The master alloy obtained by smelting is used as a master alloy to prepare nitrogen-containing nickel-based powder with a particle size of 40 to 100 μm by gas atomization, and then dried at 100° C. for 7 hours for use.
[0054] 3) Matrix treatment: Polish the nickel-based alloy matrix, rinse with alcohol and dry at 80°C for 2 hours.
[0055] 4) Plasma cladding: The process parameters were set as cladding current of 110 A, cladding speed of 3.2 mm / s, synchronous powder feeding rate of 9.8 g / min, cladding multi-pass overlap rate of 40%, plasma gas flow rate of 2.3 L / min, and powder feeding gas flow rate of 3.5 L / min to prepare a cladding layer with nitrogen-containing nickel-based powder.
[0056] The nitrogen-containing nickel-based cladding layer obtained in Example 3 is dense, uniform and crack-free. Figure 1 The samples shown were tested for bonding strength and the results are shown in Figure 1 The bonding strength is 843.4Mpa. The cladding layer was subjected to a 50h hot corrosion test in a Na2SO4+NaCl mixed molten salt at 700℃, and the corrosion weight loss was 4.6478mg / cm 2At the same time, the surface morphology and cross-sectional morphology of the cladding layer after corrosion were characterized. Figure 3-5 .
[0057] Comparative Example
[0058] The Inconel 625 alloy powder, which is the benchmark material of the nitrogen-containing nickel-based cladding layer of the present invention, has the following specific preparation steps:
[0059] 1) Powder preparation: Purchase the mature Inconel 625 alloy powder on the market, the composition of which is 22.4% chromium powder, 9.31% molybdenum powder, 4.98% niobium powder, 7.62% iron powder, 1.7% aluminum powder, and the rest is nickel powder;
[0060] 2) Matrix treatment: polish the nickel-based alloy matrix, rinse with alcohol and dry at 100°C for 1 hour;
[0061] 3) Plasma cladding: The process parameters were set as cladding current of 100 A, cladding speed of 3 mm / s, synchronous powder feeding rate of 10 g / min, cladding multi-pass overlap rate of 32%, plasma gas flow rate of 3.6 L / min, and powder feeding gas flow rate of 5.3 L / min to prepare the nitrogen-containing nickel-based powder into a cladding layer.
[0062] The nitrogen-containing nickel-based cladding layer obtained in the comparative example is dense, uniform and crack-free. Figure 1 The samples shown were tested for bonding strength and the results are shown in Figure 1 The bonding strength is 807.7Mpa. The cladding layer was subjected to a 50h hot corrosion test in a Na2SO4+NaCl mixed molten salt at 700℃, and the corrosion weight loss was 4.7423mg / cm 2 At the same time, the surface morphology and cross-sectional morphology of the cladding layer after corrosion were characterized. Figure 3-5 .
[0063] Examples 1, 2 and 3 of the present invention are the nitrogen-containing nickel-based cladding layers of the present invention, while the comparative example is the mature Inconel 625 powder on the market. Figure 1 It can be proved that the cladding layer is well bonded to the substrate. At the same time, the surface morphology and cross-sectional morphology of the cladding layer after corrosion are characterized. Figure 3-5 .
[0064] pass Figure 3 It can be seen that the corrosion weight loss of the three nitrogen-containing nickel-based cladding layers is lower than that of Inconel 625. Figure 4It can be seen that the corrosion surface of Example 1 is covered with granular corrosion products and has a small amount of corrosion holes; the surface of Example 2 is mainly large corrosion holes, and granular corrosion products are also distributed; in Example 4, almost no granular corrosion products are observed, and there are a large number of corrosion holes, forming a network structure; the corrosion surface of the comparative example also has no granular corrosion products, and large corrosion pits appear. Figure 5 It can be seen that the thickness of the corrosion layer is: Comparative Example > Example 3 > Example 2 > Example 1.
[0065] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A Pt-modified hot corrosion-resistant nitrogen-containing nickel-based cladding layer, characterized in that: The components are as follows by weight percentage: 24-26% chromium, 4-4.5% molybdenum, 4-6.5% niobium, 13-14% iron, 0.5-0.6% nitrogen, 0.15-0.3% platinum, and the rest is nickel, wherein the nitrogen is added in the form of chromium nitride.
2. A method for preparing a Pt-modified hot corrosion-resistant nitrogen-containing nickel-based cladding layer, characterized in that: The specific steps are as follows: 1) Vacuum smelting: various components are smelted into alloy blocks in proportion, and the purity of the alloy blocks is ≥99.5%; 2) Atomization powder making, obtaining alloy powder by vacuum atomization method, the particle size of the alloy powder is 30μm to 100μm, and drying for standby use; 3) Matrix treatment: polish the nickel-based alloy matrix to a bright finish, then rinse with alcohol and dry for later use; 4) Preparation of cladding layer: forming a cladding layer by plasma cladding the alloy powder.
3. The method for preparing a Pt-modified hot corrosion-resistant nitrogen-containing nickel-based cladding layer according to claim 2, characterized in that: The vacuum atomization equipment in step 2) is a ZGW-25 vacuum air atomization powder making equipment.
4. The method for preparing a Pt-modified hot corrosion-resistant nitrogen-containing nickel-based cladding layer according to claim 2, characterized in that: In the step 2), the drying temperature is 80° C. to 100° C., and the drying time is 6 to 8 hours.
5. The method for preparing a Pt-modified hot corrosion-resistant nitrogen-containing nickel-based cladding layer according to claim 2, characterized in that: The composition of the nickel-based alloy matrix in step 3) is 20.9% chromium, 8.7% molybdenum, 4.8% niobium, 4.3% iron, 0.1% aluminum, 0.4% titanium, and the rest is nickel.
6. The method for preparing a Pt-modified hot corrosion-resistant nitrogen-containing nickel-based cladding layer according to claim 2, characterized in that: In the step 3), the drying temperature is 60-110° C. and the drying time is 1-3 hours.
7. The method for preparing a Pt-modified hot corrosion-resistant nitrogen-containing nickel-based cladding layer according to claim 2, characterized in that: The plasma cladding equipment in step 4) is a DML-V03BD powder cladding machine.
8. The method for preparing a Pt-modified hot corrosion-resistant nitrogen-containing nickel-based cladding layer according to claim 2, characterized in that: In the step 4), the current of plasma cladding is 100-120A, the cladding speed is 3-4mm / s, the synchronous powder feeding rate is 9.5-10.5g / min, the plasma gas flow rate is 2-4L / min, and the powder feeding gas flow rate is 2-8L / min.
9. The method for preparing a Pt-modified hot corrosion-resistant nitrogen-containing nickel-based cladding layer according to claim 2, characterized in that: In the step 4), the overlapping rate of multiple passes of the cladding layer is 30-45%.
Citation Information
Patent Citations
A method for manufacturing seamless iron-nickel alloy tubes applicable to advanced ultra-supercritical units
CN113802041B